Influence of preload and nonlinearity of railpads on vibration of railway tracks under stationary and moving harmonic loads - Koroma, Samuel G.; Hussein, Mohammed F.M.; Owen, John S. (Sage, 2015)
In railway track dynamics, the stiffness and damping properties of railpads have a significant effect on track vibration, decay rates as well forces transmitted to the track supporting structure. Many studies have shown that railpads exhibit pronounced nonlinear behaviour, with preload and frequency dependent properties. This paper presents a three parameter railpad model, together with its differential equation of motion and the required model parameters obtained from experimental data. A time domain model of a rail discretely supported on these railpads is then formulated using the finite element method. The model is subjected to static and dynamic loading in order to study the effects of preload and frequency on its dynamic behaviour. Results are shown as time histories and frequency spectra for the track displacements and reaction forces for various preload levels. They emphasise the necessity of accounting for nonlinear behaviour based on the large disparities (up to 20 dB) observed between the linear and nonlinear cases for the parameters used in this study.